Derivação de células tronco pluripotentes induzidas a partir de pacientes com doenças mitocondriais como modelo de estudo da herança mitocondrial - Macabelli, Carolina Habermann (2015)
Mitochondrial dysfunctions caused by mutations in the mitochondrial DNA (mtDNA) represent an important group of human pathologies. However, it is not possible to predict with accuracy the risk of a woman with mutant mtDNA to transmit her pathology to her descendants. This is mainly due to out limited understanding of the molecular basis of mitochondrial inheritance. Since development of a technology that enabled derivation of induced pluripotent stem cells (iPSCs) from in vitro culture of somatic cells, iPSCs have become an interesting model to study mitochondrial inheritance. Derivation of iPSCs from patients with pathogenic mtDNA mutations has revealed that the mutant load decreases through in vitro culture of iPSCs, suggesting the existence of a specific mechanism that eliminates mutant mtDNA in the germ line. Thus, the aim of this work was to use iPSCs derived from patients with mitochondrial disorders to investigate the existence of a mechanism that eliminates mtDNA molecules with pathogenic mutations. In this way, we used heteroplasmic fibroblasts harboring a point mutation A3243G in mtDNA causing mitochondrial encephalomyopathy, lactic acidosis and stroke-like episodes (MELAS); heteroplasmic fibroblasts harboring a deletion in mtDNA causing Kearn-Sayre Syndrome (KSS) and homoplasmic fibroblasts containing only wild-type mtDNA (Control). The KSS lineage derivation resulted in iPSCs with low levels of mutant mtDNA (<0,1%), and the elimination of mutant molecules during the culture. The MELAS derivation resulted in iPSCs with high levels of mutant mtDNA (> 98%), and indication of mutant molecules elimination as well. However, unexpectedly, there was no reduction of mtDNA content in iPSCs compared to fibroblasts in all lineages. On contrary, mtDNA copy number increased in MELAS and KSS iPSCs, perhaps due to the high levels of mutations in the cells. No effect of Rapamycin (mitophagy inductor) treatment was detected on the yield of colony formation in MELAS iPSCs. Additionally, Rapamycin did not affect the mutation levels in MELAS iPSCS compared to untreated iPSCs. Finally, gene expression analysis of MELAS iPSCs provided evidences of an autophagic mechanism directed towards the mitochondrion.